Plantwide Control Design Based on the Control Allocation Approach - Luppi, Patricio Alfredo (2018)
In this work the control allocation (CA) philosophy is considered in order to propose a plantwide control (PWC) design methodology. For medium/large-scale processes for which the number of actuators is greater than the number of controlled variables, a CA-based strategy can be used to distribute the total control effort among the actuators, with some attractive features. First, the CA module can explicitly handle (i) constraints on inputs (typically actuator position and rate limits) and (ii) additional control objectives (e.g., to penalize the actuators control energy). Second, CA has the potential to provide (actuator) fault tolerance without considering a control structure reconfiguration. In this paper, a decentralized control structure is proposed for computing the total control effort, which is implemented with conventional single-input single-output PID controllers. In addition, a CA module is configured and two alternative algorithms are compared, namely, (i) generalized inverse plus simple saturation and (ii) active set method for a weighted least-squares formulation. The complete structure can be designed based on steady-state process information. The well-known Tennessee Eastman case study is considered to evaluate the proposal. Several closed-loop simulations are presented to show the dynamic performance of the PWC structure and the timing properties of the CA algorithm.